Modulation of Human Colon Cell Activity by Synthetic Coumarin Derivatives Bearing a Phosphonate Group - Katarzyna Szwaczko; Roman Paduch; Kamil Dziuba; Krzysztof Szafrański; Adrian Wiater (Molecules, 2025)
In this paper, we will present the synthesis of coumarins bearing a phosphonate group in the C-3 position of the coumarin skeleton and phosphacoumarin derivatives. The compounds were synthesized by Knoevenagel condensation. Notably, the synthetic difficulties in preparing phosphacoumarins have limited previous studies. Our approach allows us to efficiently produce these derivatives, opening the way to investigate their biological properties. The resulting compounds were fully characterized using spectroscopic techniques and high-resolution mass spectrometry. We then evaluated the cytotoxicity of the compounds against human colon cancer HT-29 tumor and CCD 841 CoTr normal colon epithelial cells. We compared these results with coumarin activity to assess the effect of the introduction of the phosphonate group on their cytotoxicity. In addition, we performed cell cycle analysis by flow cytometry and examined the antioxidant activity of the compounds by the DPPH and FRAP methods. Furthermore, we conducted ADME analysis to gain more insight into the pharmacokinetic properties of the tested coumarins. Our study is in line with current trends in the search for new compounds with potential anticancer properties. Although there are numerous reports in the scientific literature on the anticancer activity of coumarin derivatives, the cytotoxicity of synthetic derivatives with a phosphonate group has not been investigated to date.